Evaluation of knowledge, attitude and behavior of Turkish university students regarding family planning - Fatma Fidan; Dilek Aygin (Universidade Federal de Goias, 2012)
Research conducted to define general knowledge of university students' attitudes and behaviors about family planning. The sample consisted of 755 Sakarya University students. Data were collected from an open-ended questionnaire form and faceto-face interviews. The data analysis process was conducted using specific software. Most participants (59.7%) were over 22 years old and female, and 1.2 % of the females were married. Women in the study had a positive outlook regarding the positive effects of family planning on sexual health and stated that family planning is important to both society and our economy. The awareness and knowledge regarding family planning was found to be strongest among older participants. The family planning concept was understood correctly by about half of the students. Finally, young people did not have sufficient knowledge about family planning, its methods or where to obtain information on the topic.